Tunneling Incentive, Mekanisme Bonus dan Pengaruhnya Terhadap Tranfer Pricing Dengan Tax Minimization Sebagai Variabel Moderasi - Samino Hendrianto; Nursimah Dara; Masturo Masturo (Departement of Mathematics Education, 2023)
The aim of this research is to determine tunneling incentives, bonus mechanisms and their influence on transfer pricing with tax minimization as a moderating variable. The research time period used was 5 years, namely the 2018-2022 period. The research population is food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique uses purposive sampling technique. Based on the predetermined criteria, 17 companies were obtained. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The analytical method used is panel data regression analysis using Eviews 12. The research results show that Tunneling Incentive and Tax Minimization have an effect on Transfer Pricing, Tax Minimization can moderate Tunneling Incentive on Transfer Pricing. The Bonus Mechanism has no effect on Transfer Pricing and Tax Minimization cannot moderate the Bonus Mechanism on Transfer Pricing.